2012
DOI: 10.1002/jcu.21993
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of percutaneous core needle biopsy in diagnosing papillary breast lesions and potential impact of sonographic features on their management

Abstract: Although some sonographic features could favor a benign diagnosis, when a core biopsy yields the diagnosis of a papillary lesion, surgical excision is recommended to definitely exclude malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
(54 reference statements)
0
5
1
Order By: Relevance
“…Among them, 36 (73.5%) were removed surgically or by vacuum‐assisted biopsy, and only one was upgraded to DCIS. This low upgrade rate (2.8%) is in stark contrast to that of the study on the accuracy of CNB in diagnosing papillary breast lesions by Al Hassan et al, in which the upgrade rate to malignancy from papillomas was 9.7%. We attribute the difference to the different mode of detection; our population was composed of asymptomatic US‐detected lesions, whereas the population in the other study consisted of a combination of patients with symptomatic lesions or mammography‐detected lesions.…”
Section: Discussioncontrasting
confidence: 80%
“…Among them, 36 (73.5%) were removed surgically or by vacuum‐assisted biopsy, and only one was upgraded to DCIS. This low upgrade rate (2.8%) is in stark contrast to that of the study on the accuracy of CNB in diagnosing papillary breast lesions by Al Hassan et al, in which the upgrade rate to malignancy from papillomas was 9.7%. We attribute the difference to the different mode of detection; our population was composed of asymptomatic US‐detected lesions, whereas the population in the other study consisted of a combination of patients with symptomatic lesions or mammography‐detected lesions.…”
Section: Discussioncontrasting
confidence: 80%
“…A meta‐analysis rescreening studies conducted between January 1985 and March 2012 demonstrated a substantial risk of upgrading after surgical excision for CNB‐diagnosed non‐malignant breast papillary lesions, with a pooled underestimation rate of 15.7% . Subsequent studies reported a range of 3–33% of CNB‐diagnosed benign papillary lesions being upgraded to atypical or malignant categories in surgical excision or imaging follow‐up . A topographical and histopathological study found that ~25% of DCISs associated with papilloma had a potential risk of sampling error in small samples of CNBs, owing to an eccentric distribution or a low proportion of DCIS within the papilloma, whereas radiology showed segmental abnormalities in 83% of these cases …”
Section: Practical Issues With Papillary Lesions Of the Breastmentioning
confidence: 99%
“…The standard management for malignant and atypical papillary lesions is surgical excision [11]. However, subsequent management of a benign PBL is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies consider intraductal papillomas to be benign lesions without malignant potential or risk for developing a subsequent carcinoma. Others recommend the surgical removal of all papillary lesions, including benign due to a high association between breast cancer and papillomas [2, 11]. This recommendation is based on the probability of up to 24.5% of the benign PBLs upgrade to malignant [5].…”
Section: Introductionmentioning
confidence: 99%